Improvements in the reduction coagulation filtration process for hexavalent chromium treatment. Issue 1 (6th January 2023) - Gorman, Craig; Kennedy, Anthony; Samson, Carleigh; Plummer, Sarah; Townsend, Eli; Seidel, Chad
Abstract: Reduction coagulation filtration using ferrous iron (Fe(II)‐RCF), or reduction filtration using stannous tin (Sn(II)‐RF), for the removal of hexavalent chromium (Cr(VI)) from drinking water represent attractive alternatives to ion exchange or reverse osmosis. With a new maximum contaminant level for Cr(VI) anticipated in California, this study sought to expand on previous research by applying Fe(II)‐RCF and Sn(II)‐RF to multiple groundwaters under a variety of reductant dose and reduction time scenarios. Four different granular filter media were also tested for removal of total chromium (Cr(T)) following Cr(VI) reduction to trivalent chromium (Cr(III)). Sodium hypochlorite, instead of aeration, was used to oxidize excess Fe(II) to Fe(III) prior to filtration, with minimal Cr(III) to Cr(VI) reoxidation. Sn(II)‐RF was also able to achieve Cr(T) and Cr(VI) treatment goals without dedicated reduction time prior to filtration. Results of this study were used to develop more up‐to‐date, feasibility‐level, 20‐year annualized cost estimates.